SEG Technical Program Expanded Abstracts 2014 2014
DOI: 10.1190/segam2014-1126.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismo-acoustic characterization of a seismic vibrator

Abstract: A seismic vibrator generates seismic and acoustic noise as soon as it is pressured up and located in the proximity of a recording spread. The noise in the seismic bandwidth is more critical in vibroseis surveys where a large number of vibrators are used as in the case of simultaneous acquisitions. The noise in the acoustic bandwidth is particularly important when the survey takes place in populated areas. We carried out a seismo-acoustic experiment to characterize these noises. We present the results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…All the aforementioned analyses, and the FT domain harmonic distortion analysis shown in Figures 14 and 15, were enabled by the four e-vib built-in accelerometers (three on the reaction mass and one on the base plate). The harmonic distortion analysis indicates that the harmonic distortion was slightly less on asphalt compared to grass, and that total harmonic distortion levels for the ground force (Figure 15c), which is representative for the vibrator internally, are generally quite low and likely lower than for a hydraulic vibrator (Bagaini, 2008;Wei et al, 2010;Wei and Hall, 2011;Wei and Phillips, 2013;Bagaini et al, 2014). However, given that the e-vib has a peak force of only 6.7 kN, to support these claims, further analyses and a side-by-side comparison between the e-vib and a hydraulic vibrator at comparable force levels and same acquisition parameters are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the aforementioned analyses, and the FT domain harmonic distortion analysis shown in Figures 14 and 15, were enabled by the four e-vib built-in accelerometers (three on the reaction mass and one on the base plate). The harmonic distortion analysis indicates that the harmonic distortion was slightly less on asphalt compared to grass, and that total harmonic distortion levels for the ground force (Figure 15c), which is representative for the vibrator internally, are generally quite low and likely lower than for a hydraulic vibrator (Bagaini, 2008;Wei et al, 2010;Wei and Hall, 2011;Wei and Phillips, 2013;Bagaini et al, 2014). However, given that the e-vib has a peak force of only 6.7 kN, to support these claims, further analyses and a side-by-side comparison between the e-vib and a hydraulic vibrator at comparable force levels and same acquisition parameters are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…These odd harmonics (3rd, 5th, etc.) can often be prominent in hydraulic vibrators (Bagaini et al, 2014). As discussed in detail by Noorlandt et al (2015), other harmonics and system resonances, in particular associated with the air spring, have successfully been modeled and a suppression mechanism has been developed.…”
Section: Lsm-driven Seismic Vibratormentioning
confidence: 99%
See 1 more Smart Citation
“…The source weighs approximately 1650 kg, operates at a constant drive level with a peak force of 7 kN and requires 14 kW of power to operate. The absence of hydraulics, combined with the frictionless guidance system of the LSMs behind the E‐Vib overcome some of the intrinsic limitations of the hydraulic vibrators (Sallas, 2010; Bagaini et al ., 2014; Brodic et al ., 2021a). To support this, in studies conducted by Sallas (2010) it was found that more than two third of the power produced by a hydraulic vibrator engine is transferred as heat, thus not usable.…”
Section: The Electromagnetic Vibratormentioning
confidence: 99%